Health inequalities in a middle-income country: a systematic review of the Costa Rican case - Barboza-Solis, Cristina; Herrero, Rolando; Fantin, Romain (Frontiers in Public Health, 2024)
Objective: This study systematically reviews evidence of socioeconomic health disparities in Costa Rica, a middle-income country, to elucidate the relationship between socioeconomic status and health outcomes.Methods: Published studies were identified through a systematic review of PubMed (English) and Scielo (Spanish) databases from December 2023 to January 2024, following PRISMA guidelines.Search terms included socioeconomic status, social determinants, social gradient in health, and health inequalities.Results: Of 236 identified references, 55 met the inclusion criteria. Findings were categorized into health inequalities in mortality (among the general population, infants, and older adults), life expectancy, cause-specific mortality, and health determinants or risk factors mediating the association between the social environment and health. The studies indicate higher mortality among the most disadvantaged groups, including deaths from respiratory diseases, violence, and infections. Rosero-Bixby and Dow (2016) found that higher socioeconomic status was associated with lower mortality rates in the 1990s, indicating a positive social gradient in health (RII=1.3, CI [1.1-1.5]. Disparities were less pronounced among older adults. Urban areas exhibited concentrated wealth and increased risky behaviors, while rural areas, despite greater socioeconomic deprivation, showed a lower prevalence of risky behaviors. Espinoza-Aguirre et al.(2020) showed that people living in rural areas smoked significantly less than those in urban areas (7% vs. 10%). Despite the relatively equitable distribution of public primary healthcare, disparities persisted in the timely diagnosis and treatment of chronic diseases. Fantin et al. (2020) observed that cancer survival rates post-diagnosis were positively correlated with the wealth of districts (1.23 [1.12-1.35] for all cancers combined).The study highlights the existence of social health inequalities in Costa Rica.However, despite being one of the most unequal OECD countries, Costa Rica shows relatively modest social gradients in health compared to other middle and high-income nations. This phenomenon can be attributed to distinctive social patterns in health behaviors and the equalizing influence of the universal healthcare system.